Correlation Between the Baby Blues Syndrome and Postpartum Depression among Mother - Wati, Linda; Amran, Amrina; Ilmaskal, Radian (Journal of Health Sciences and Epidemiology, 2025)
Baby blues syndrome, while often considered mild and self-limiting, may increase the risk of postpartum depression if left unrecognized. This study aimed to examine the association between baby blues and the incidence of depression in postpartum women. This cross- sectional study was conducted at Mutiara Bunda Hospital, Padang City, from June to November 2024. A total of 178 postpartum women were selected using simple random sampling. The inclusion criteria were women 4–6 weeks postpartum. Women with a history of psychiatric illness, current use of psychotropic medication, major obstetric complications, or neonatal death were excluded. Baby blues syndrome and postpartum depression were assessed using the Kennerley–Gath Maternity Blues Questionnaire (KBQ) and the Edinburgh Postnatal Depression Scale (EPDS). Data were analyzed using the chi-square test. Of 178 participants, 95 (53.4%) experienced baby blues and 49 (27.5%) were identified as having postpartum depression. Among those with baby blues, 38.9% developed postpartum depression, compared to 14.5% among those without baby blues. Chi-square analysis revealed a significant association between baby blues and postpartum depression (p < .001). The findings indicate that baby blues syndrome is significantly associated with an increased risk of postpartum depression. Early identification and monitoring of baby blues are critical in preventing the progression to more severe maternal mental health disorders. Integrating baby blues screening into routine postpartum care may improve mental health outcomes in maternal health services.